One step production of phosphorene from red phosphorus and investigation of their supercapacitor applications with conducting polymers - Yilmaz, Ozan; Kalyon, Hilal Yildirim; Gencten, Metin; Sahin, Yucel (ELSEVIER, 2024)
In this work, phosphorene, which was used as an additive to the conductive polymer (polyaniline), was produced in a single step using the chemical method at 80 degrees C in 6 h for the first time in the literature. In addition, composites of polyaniline with phosphorene have also been produced for the first time in the literature, and these materials have been used as electrode materials in supercapacitors. The parameters of supporting electrolyte concentration, monomer concentration and cycle number, which are the factors affecting the success of electrochemical synthesis, were optimized and the optimum values for these parameters were determined for polymers. The structural and morphological properties of the produced 2D phosphorene were investigated using spectroscopic and microscopic methods. After that, phosphorene was simultaneously and electrochemically incorporated into the structure of polyaniline (Pani), which was produced by the electrochemical method, likewise. Finally, the phosphorene-based materials produced have been used as electrode components in supercapacitors. Hybrid supercapacitor electrodes (Phosphorene@Pani/PGEs) were characterized by cyclic voltammetry and electrochemical impedance spectroscopy methods and the changes in the capacitive behavior of these systems according to the number of cycles were examined using the galvanostatic charge-discharge technique. Specific capacitance value of phosphorene-doped composite material was 335.54 F & sdot;g- 1 at a chargedischarge current density of 1.6 A & sdot;g- 1.Capacitance retention of the composite material was 85 % at end of 1000 cycles with 1.6 A & sdot;g- 1. It was also around of 80 % after 4000 cycles with 2.5 A & sdot;g- 1 charge/discharge current densities. A significant increase in specific capacitance of 259.21 % was seen when compared with the electrode without phosphorene added. By adding of phosphorene in the conducting polymer structure, specific capacitance of the system is improved.
Keywords: Phosphorene; Supercapacitor; Energy storage systems; Two-dimensional materials; Conductive polymers; Red phosphorus; SOLID-STATE SUPERCAPACITORS; BLACK-PHOSPHORUS; ELECTRODE MATERIAL; ENERGY-STORAGE; HYBRID; POLYPYRROLE; COMPOSITE; Energy & Fuels